Efficacy of fermented grain using Bacillus coagulans in reducing visceral fat among people with obesity: a randomized controlled trial - Cho, Eunbyul; Kim, Ju Young; Cho, Belong; Lee, Joong Su; Yoon, Yeo Cho; Shin, Yong Chul; Kim, Hyerim; Gil, Siye; Kim, Sohye (Frontiers in Nutrition, 2023)
Background Obesity is a socioeconomic problem, and visceral obesity, in particular, is related to cardiovascular diseases or metabolic syndrome. Fermented grains and various microorganisms are known to help with anti-obesity effects and weight management. Studies on the relationship between Bacillus coagulans and anti-obesity effects are not well known, and studies on the application of fermented grains and microorganisms to the human body are also insufficient. Objectives This study aimed to evaluate the efficacy of Curezyme–LAC, an ingredient mixed with six-grain types fermented by B. coagulans, in reducing fat mass in adults with obesity. Methods In this randomized double-blinded placebo-controlled study, 100 participants [aged 40–65 years; body mass index (BMI) ≥ 25 to ≤ 33 kg/m2) were randomly allocated to two groups: 4 g/day Curezyme–LAC administered as a granulated powder or placebo (steamed grain powder mixture). Results After 12 weeks, visceral adipose tissue decreased significantly in the Curezyme–LAC group compared with that in the placebo group (mean ± standard error, SE of −9.3 cm2 ± 5.1) vs. (6.8 cm2 ± 3.4; p = 0.008). Compared to the placebo group, the Curezyme–LAC group also showed significant reductions in total fat mass (−0.43 ± 0.24 kg vs. 0.31 ± 0.19 kg, p = 0.011), body weight (−0.4 ± 0.3 kg vs. 0.3 ± 0.2 kg, p = 0.021), BMI (−0.14 ± 0.12 vs. 0.10 ± 0.07, p = 0.028), and waist circumference (−0.6 ± 0.2 cm vs. −0.1 ± 0.2 cm, p = 0.018) without a change in dietary intake and physical activity. Conclusion Curezyme–LAC supplementation for 12 weeks may benefit individuals with obesity by reducing visceral fat mass.